Aprisionamento disfarçado de refinamento : Considerações sobre o ensino de “arte” para mulheres no século XIX - Ribeiro , Diego; Costa , Thays Alves (Revista do Colóquio, 2023)
This article aims to reflect on the teaching of “art” to women in the 19th century, based on the considerations of the Brazilian author Ana Mae Barbosa, regarding the idea of ​​artistic practices as symbols of refinement for women from the elites. In this brief study, we intend to observe the teaching of “art” as a form of imprisonment disguised as refinement, since artistic practices were seen as almost obligatory for young women who intended to marry.